ANALISA PENGARUH EMOTIONAL MARKETING TERHADAP PURCHASE INTENTION MELALUI BRAND AWARENESS PADA PRODUK DOVE PERSONAL CARE DI SURABAYA - Irene Susilo; Hatane Semuel (Institute of Research and Community Outreach - Petra Christian University, 2015)
Emotional Marketing is a new concept in the world of marketing with the aim of giving the impression of a unique emotional side featuring a brand or product. The purpose of this research is to analyze how the influence of emotional marketing towards Purchase Intention through brand awareness. Objects that will be examined in this study is the product of Dove personal care. This type of research is causal explanatory using the GSCA data measurement techniques. The sample in this research totalled 100 respondents, namely the community shown ads Dove. Sampling techniques in the research of using the technique of judgemental sampling. The type of collection of data in this study using a detailed questionnaire to a sample of research dissemination. Results of the study prove that emotional marketing the Dove had done against direct influence brand awareness and purchase intention but different case with Brand awareness has no effect directly against Purchase Intention.